From financial to real economic crisis. Evidence from individual firm-bank relationships in Germany - Nadja Dwenger; Frank Fossen; Martin Simmler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
What began as a financial crisis in the U.S. in 2007/8 quickly became a massive crisis of the global real economy. We investigate the importance of the bank lending and firm borrowing channel in the international transmission of bank distress to the real economy, in particular to firm investment. We exploit a unique data set for Germany which contains financial statements at the level of the firm for the period 2004 2010 together with the financial statements of each firm s relationship bank(s). The data include small and medium sized firms. Using instrumental variable estimations in first differences to eliminate firm- and bank-specific effects, we find that banks which were affected at the onset of the financial crisis due to proprietary trading activities cut back lending more strongly relative to non-affected banks. Firms whose relationship banks reduce lending downsize real investment significantly. The effect tends to be larger for smaller and younger firms as well as for firms unable to provide much collateral. We also document that some of the firms partially offset reduced credit supply by using up internal funds, by issuing new equity, and by establishing new bank relationships.
Keywords: D22; D92; G01; 330